Paper 63: Remodeling of Adolescent Displaced Clavicle Fractures: A FACTS Study. Issue 7 (30th July 2022) - Bae, Donald; Boutelle, Kelly; Busch, Michael; Carroll, Alyssa; Edmonds, Eric; Ellis, Henry; Hergott, Katelyn; Kocher, Mininder; Li, G. Ying; Nepple, Jeffrey; Pandya, Nirav; Perkins, Crystal; et al.
Objectives: The phenomenon of bony remodeling of healed displaced clavicle midshaft fractures in adolescents remains poorly understood. The purpose of the current study was to evaluate and quantify clavicle remodeling in a large population of adolescents with completely displaced fractures treated non-operatively to understand the factors that may influence this process. Methods: Patients were identified from the database(s) of a multi-center study group investigating the functional outcomes of adolescent clavicle fractures. Patients between the ages of 10 and 19 years with completely displaced mid-diaphyseal clavicle fractures that were treated non-operatively who had further imaging of the affected clavicle at a minimum of 9 months from initial injury were included. Radiographic measurements were performed on the injury and final follow-up films. Fracture remodeling was subjectively classified as 'complete/near-complete', 'moderate', or 'minimal' (Figure 1) and subsequently analyzed quantitively and qualitatively to determine factors associated with deformity correction. Results: Ninety-eight patients (mean age of 14.4±2.2 years) were analyzed at a mean radiographic follow-up of 3.4± 2.3 years. Fracture shortening, superior displacement, and angulation significantly improved during the follow-up period by 59%, 61%, and 30% respectively (p<0.001). Fracture remodeling was found to be associated with follow-up time; those with longer follow-up time demonstrate more remodeling (p<0.001). Ninety-two percent of patients <14 years and 79% of patients ³14 years-old at time of injury with a minimum follow-up of four years underwent complete/near-complete remodeling. Conclusions: Significant clavicle remodeling occurs in adolescent patients with displaced fractures, including older adolescents and particularly when followed for longer time intervals. This finding may help explain why symptomatic malunions are so infrequently observed in adolescent patients, even in severely displaced fractures.